Diffusion of Innovation: Application of Interactive Learning Media in PPKn Subjects in Junior High School - Pandu Rudy Widyatama; Jayan Trianus; Sri Utami (JED (Jurnal Etika Demokrasi), 2024)
The aim of this research is now realized to improve the quality of advanced education and the creation of digitalization of education. The study used a literature review to examine the application of interactive learning media in PPKn subjects in junior high schools (SMP). This research uses a qualitative approach. The findings in this research are of the analysis, which shows that 50% of the interactive media used by researchers in PPKn subjects are quiz games-based, namely by utilizing the Quizizz platform, Crossword Puzzle method, and independent applications. In addition, the results of the analysis showed that 60% of researchers applied interactive learning media to PPKn subjects to increase students' learning willingness (interest in learning, motivating, and increasing willingness to read). The cocclusion importance of diffusion of innovation in education in the form of the application of interactive learning media the interest of students in learning so that the realization of the nation's ideals is to educate the nation's life.